PENGUASAAN KOSAKATA BAHASA ARAB DAN BUDAYA MAKASSAR DENGAN E-KTP (ELEKTRONIK KARTU PINTAR) - Akhriani Akhriani; Asmara Asmara; Hikmah Hikmah; Agussalim Agussalim (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The purpose of this study is to describe the results of the development of learning media in Arabic and cultural Makassar using card media. This study uses research and development methods that combine qualitative and quantitative methods. The results of this study produce card learning media that are integrated with information technology based on qr code. The results of this study indicate the compatibility between learning media and information technology, as evidenced by the application of four language skills in one card. The test results of experts showing card learning media with the help of information technology showed good results on the use, material and face-to-face appearance.